2010
DOI: 10.1002/mrc.2676
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the direct synthesis of tryptophan from indole and serine: a useful NMR technique for the detection of a reactive intermediate in the reaction mixture

Abstract: The reaction mechanism for the biomimetic synthesis of tryptophan from indole and serine in the presence of Ac(2)O in AcOH was investigated. Although the time-course (1)H-NMR spectra of the reaction of 5-methoxyindole with N-acetylserine were measured in the presence of (CD(3)CO)(2)O in CD(3)CO(2)D, the reactive intermediate could not be detected. This reaction was conducted without 5-methoxyindole in order to elucidate the reactive intermediate, but the intermediate could not be isolated from the reaction mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Unfortunately, -elimination of the SCF 3 group could not be avoided, even under mild basic conditions, [27] and a significant amount of elimination product 8 [28,17] was always obtained beside the expected amino acid 7 (Scheme 1). We first tried saponification of the cysteine methyl ester derivative 4a.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, -elimination of the SCF 3 group could not be avoided, even under mild basic conditions, [27] and a significant amount of elimination product 8 [28,17] was always obtained beside the expected amino acid 7 (Scheme 1). We first tried saponification of the cysteine methyl ester derivative 4a.…”
Section: Resultsmentioning
confidence: 99%
“…Along these lines, 2‐methyl‐4‐methylenoxazol‐5(4 H )‐one has been proposed as a key Michael acceptor intermediate in the biomimetic synthesis of N ‐acetyl‐4‐bromotryptophan en route to clavicipitic acids . In further studies, such a highly reactive type‐2 alkene was found to be formed in situ from serine and acetic anhydride and could be detected in solution by NMR spectroscopy . However, and unlike 4‐ethyliden‐ and especially 4‐benzylidenoxazol‐5(4 H )‐ones, which have been profusely synthesised and used in organic synthesis, the 4‐methylidene analogues have remained very elusive to both synthesis and application, due to their very low stability.…”
Section: Figurementioning
confidence: 99%
“…The same results were obtained with N , N′ ‐dicyclohexylcarbodiimide (DCC) and N , N′ ‐diisopropylcarbodiimide (DIC) as carboxylic acid activators. Careful monitoring of the reaction between 1 and DIC in CDCl 3 by 1 H NMR (Figure ) showed the fast disappearance of the starting material signals and the appearance of two narrow doublets in the 6.00–6.20 ppm region associated with methylene protons, reaching its maximum level of conversion of 90 % in 15 min. Thus, it was clear that 4‐methylene‐2‐phenyloxazol‐5(4 H )‐one (MPO, 2 ) is formed immediately through DIC‐promoted cyclisation and subsequent β‐elimination of benzoic acid, although this compound is too reactive to be isolated through a conventional workup.…”
Section: Figurementioning
confidence: 99%
“…Due to our experience developing unprotected synthesis strategies for highly polar compounds such as free amino acids, [14][15][16][17] we attempted the direct introduction of benzyl acetate moiety into unprotected diol 3.…”
Section: Synthesis Of Vip-lipopeptide Using a New Linker To Modify LImentioning
confidence: 99%